PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS NEARPOD PADA MATERI PLANET-PLANET DI TATA SURYA UNTUK SISWA KELAS VI SEKOLAH DASAR - Pangestu, Muhammad Abdul; Hermita, Neni; Fendrik, Muhammad (Tunjuk Ajar: Jurnal Penelitian Ilmu Pendidikan, 2024)
This research is research and development aimed at developing Nearpod-based learning media regarding the planets in the solar system for elementary schools. This research uses a 4D development model, there are define, design, development and dissemination. This research was conducted on sixth grade students at SDN 194 Pekanbaru in the term of 2023/2024. The data collection techniques used were interview sheets, validation and practicality questionnaires. The data analysis technique used were descriptive qualitative analysis which is used to analyze data in the form of suggestions and input provided by expert validators from media suitability validation sheets. The results from the media validity test show that this media is categorized as very valid with a score 89.48%. This media development said to be very valid seen criteria from the product, material and language aspects. After conducting small group trials to see the practicality of the media developed, it can be concluded that this media is very good with a score of 90.5% obtained from teacher and student responses. From the validity and practicality results, it can be concluded that Nearpod-based media regarding the planets in the solar system in elementary schools is declared valid and very practical.